Estimation of OAE Properties. Ensemble Correlation Method for SNR Enhancement in TEAOE Signals - Janusauskas, A.; Engdahl, B.; Svensson, O.; Sörnmo, L. (Elektronika ir Elektrotechnika, 1999)
New method for OAE signal processing is presented here. Method is based on signal decomposition into frequency components, ensemble correlation method, applied to extract information about individual and mean behaviour of OAE signal; and the use of various window functions. Comparison of all methods is provided. New methods are also compared to those used in commercial equipment "ILO92". The performance of each approach is estimated on extensive OAE signals database which were collected during the health screen in Norway, 1997. Evaluation criterion is ability to detect normal hearing and hearing impaired subjects.